Work family conflict, mental wellbeing, and social support among doctors in Pakistan - Kayani, Tooba; Irfan, Siddrah (Journal of the Pakistan Medical Association, 2026)
Objective: To find out the relationship among social support, mental wellbeing and work-family conflict. Methods: The cross-sectional, correlational study was conducted at hospitals in Rawalpindi, Islamabad, Lahore, Swat, Kallar Kahar and Peshawar, Pakistan from December 2021 to August 2022, and comprised healthcare providers (HCP) associated with hospitals, who had at least one year of experience in their respective field. Data was collected using the Work Family Conflict scale, the Mental Health Continuum-Short Form and the Multidimensional Scale of Perceived Social Support. Data was analysed using IBM SPSS-23. Results: Of the 154 subjects, 93(60.4%) were females, 117(76%) were aged 24-34 years, 76(49.4%) had professional experience 2-6 years, and 96(62.3%) had contracted coronavirus disease-2019. It was found that WFC has significant negative relationship with emotional wellbeing, mental wellbeing is significantly positively related to social support (r=.460**) received from family (r=.335**), friend (r=.413**) and significant others (r=.412**). Moreover, relationship between study variables and demographic variables shows significant positive relationship of mental wellbeing with age (r=.220**) and monthly income (r=.255**), WFC significant negative relationship with worked in COVID wards (r=-181*) and number of children (-.168*), and social support is negatively related to working hours per week (r=-.233**). Conclusion: Work-family conflicts led to stress among healthcare providers, affecting impacts their mental wellbeing. Social support helped in decreasing the impact of work-family conflict and helped improve the mental wellbeing of healthcare providers. Key Words: Work-family conflict, Emotional wellbeing, Social wellbeing, Psychological wellbeing, Social support.